The Breeding, Cultivation, and Potential Applications of Ornamental Orchids with a Focus on Phalaenopsis—A Brief Review - Chenjing Han; Fei Dong; Yu Qi; Yenan Wang; Jiao Zhu; Binghai Li; Lijuan Zhang; Xiaohui Lv; Jianghui Wang (Plants)
The Phalaenopsis genus, a horticulturally vital group within the Orchidaceae, dominates global floriculture markets through strategic cultivar innovation, scalable propagation, and data-driven cultivation. This review systematically examines the breeding, propagation, cultivation management, and potential applications of Phalaenopsis while providing insights into future research directions. The main contents include the following: Breeding innovations—This review outlines the taxonomy of the Phalaenopsis genus and highlights its intergeneric hybridization potential, which offers vast opportunities for developing novel horticultural varieties. By establishing clear breeding objectives, researchers employ diverse breeding strategies, including conventional crossbreeding and biotechnological approaches (e.g., mutation breeding, ploidy manipulation, genetic transformation, and CRISPR/Cas9 editing). Propagation and cultivation management—Analyses of Phalaenopsis tissue culture protocols covering explant selection, media optimization, and regeneration systems are summarized. Key factors for efficient cultivation are discussed, including temperature, light, water, nutrient management, cultivation medium selection, and integrated pest/disease management. Scientific environmental control ensures robust plant growth, synchronized flowering, and high-quality flower production. Emerging applications—Phalaenopsis exhibits promising applications in functional bioactive compound extraction (e.g., antioxidants and antimicrobial agents). This review summarizes current advancements in Phalaenopsis breeding, cultivation, and potential applications. Based on technological progress and market demands, future research directions are proposed to support the sustainable development of the Phalaenopsis industry.